Modulation Coding Scheme Performance Analysis (Mcs) Wireless 802.11ac Indoor At 5 Ghz Frequency In West And East Telecommunication Labs Politechnic State Of Semarang - Dimas Tampan Setiadi (Politeknik Negeri Semarang, 2018)
Modulation Coding Scheme or MCS is a value that specifies the modulation, coding and number of spatial streams and produces a fixed rate data rate based on channel conditions and RSSI values received by the user. Modulation on MCS there are 5 kinds of BPSK, QPSK, 16 QAM, 64 QAM and 256 QAM. While the coding rate there are 4 kinds of ½, 2/3, ¾ and 5/6. MCS and RSSI. Changes can not be separated from wireless propagation that includes Large Scale Propagation and Small Scale Fading in particular the existence of obstacles in the form of objects and indoor or outdoor areas. Test results show that major changes to RSSI are influenced by indoor or outdoor areas. MCS changes are uncertain and not RSSI based. MCS and RSSI will change based on channel conditions.